인천에서 서식지 환경과 토지 이용이 청개구리 (Hyla japonica) 수도에 미치는 영향 - 박소현(So Hyun Park); 조현석(Hyunsuk Cho); 진승남(Seung-Nam Jin); 조강현(Kang-Hyun Cho) (Ecology and Resilient Infrastructure, 2017)
The damage and fragmentation of habitat due to urbanization pose a great threat to amphibians worldwide. To understand the effect of urbanization on the distribution and abundance of Hyla japonica, we measured their population sizes by listening frog calling and investigated the habitat their population sizes and land use in the 18 rice paddy fields located in Incheon and its surroundings. Abundance of H. japonica was 0 - 17 male adults / habitat or 0 - 41 male adults / ha in Incheon. The number of the frog was increased as the distance between the habitat and the road became longer or the ratio of circumstance / area of the habitat increased. Unlike the general prediction, the density of H. japonica showed a negative correlation with the size of the habitat and a positive correlation with the surrounding land use intensity. Our results suggested that H. japonica could be concentrated in a narrow habitat due to the habitat size decrease and the periphery development according to the urbanizaion. 도시화로 인한 서식지의 훼손과 단편화는 전세계적으로 양서류에게 큰 위협이 되고 있다. 본 연구에서는 도시화가 청개구리의 분포와 수도에 미치는 영향을 파악하고자, 인천와 그 주변에 위치한 18개 논에서 청음으로 청개구리의 수도를 측정하고 서식지 환경과 토지 이용을 조사하였다. 인천과 주변 논에서 청개구리의 수도는 0 - 17마리 / 서식지 또는 0 - 41마리 / ha이었다. 청개구리의 수도는 서식지와 도로와의 거리가 멀어짐에 따라서 서식지의 둘레길이 면적이 켜질수록 증가하였다. 일반적인 예측과는 달리 청개구리의 밀도는 서식지의 크기와 음의 상관을, 주변의 토지이용 강도와는 양의 상관관계를 보였다. 따라서 도시화에 의하여 서식지 면적이 감소하고 주변이 개발됨에 따라서 청개구리리가 좁은 서식지로 집중화될 수 있다고 생각된다.